2019
DOI: 10.2138/am-2019-6844
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the discovery of new minerals over the last century

Abstract: Patterns in the discovery and description of new minerals over the last century emerge from a new database of 4,046 mineral discovery reports (roughly ¾ of all known minerals). The number of new minerals discovered per year was steady over time from 1917 to the early 1950s, when it began a rapid increase punctuated by spikes in 1962-1969, 1978-1982, and 2008-2016, the last of which is probably still ongoing. A detailed breakdown of the technological, geographic, institutional, and other characteristics of mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
(38 reference statements)
0
5
0
Order By: Relevance
“… Hystad and colleagues [ 38 ] have demonstrated that more than 3000 additional mineral species on Earth exist, but have yet to be discovered and described. New mineral species are being discovered at a rate of approximately 100 species per year [ 39 ], and many of those display complex, previously unknown structures [ 34 , 40 ]. …”
Section: Discussionmentioning
confidence: 99%
“… Hystad and colleagues [ 38 ] have demonstrated that more than 3000 additional mineral species on Earth exist, but have yet to be discovered and described. New mineral species are being discovered at a rate of approximately 100 species per year [ 39 ], and many of those display complex, previously unknown structures [ 34 , 40 ]. …”
Section: Discussionmentioning
confidence: 99%
“…With more than 6,000 different mineral species approved by the IMA-CNMNC and 100 new species discovered yearly ( 46 ), it might seem that Earth's mineral kingdom is remarkably well endowed. However, that view misses a key property of evolving systems: As with all other evolving systems, the known mineral kingdom represents only a miniscule fraction of all conceivable configurations—by our rough estimation fewer than one stable mineral occurs in every 10 42 possible element combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in the rate of new mineral descriptions are often attributed to technological advances (Barton, 2019). However, the last two decades have seen a significant jump forward in analytical techniques, especially related to X-ray and electron diffraction, enabling the analysis of much smaller crystals, measuring only a few tens of micrometres across or even smaller.…”
Section: Discussion – Chemical Composition Of Uranyl Sulfates Their F...mentioning
confidence: 99%